Equilibrium and inefficiency in fixed rate tenders - Christian Ewerhart; Nuno Cassola; Natacha Valla (European Central Bank (ECB), 2005)
The fixed rate tender is one of the main procedural formats relied upon by central banks in their implementation of monetary policy. This fact stands in a somewhat puzzling contrast to the prevalent view in the theoretical literature that the procedure, by fixing interest rate and quantity at the same time, does not allow a strategic equilibrium. We show that an equilibrium exists under general conditions even if bidders expect true demand to exceed supply on average. The outcome is typically inefficient. It is argued that the fixed rate tender, in comparison to other tender formats, may be an appropriate instrument for central bank liquidity management when market conditions are sufficiently calm.
Keywords: D44; E52; 330; equilibrium; Fixed rate tenders; inefficiency; rationing; Offenmarktpolitik; Zinspolitik; Auktionstheorie; Ungleichgewichtsökonomie; Theorie